2018
DOI: 10.31873/ijeas.5.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of High Level Sound Generated in Boiler tube Bank Duct

Abstract: Heat exchangers and boilers are widely used in various plants such as power plants and chemical plants. In heat exchangers and boilers, tube banks are set in a duct such that water passes through inside the tubes and warm gas outside the tubes. Due to the external flow around tube banks, the resonance phenomenon called the self-sustained tone occurs at a certain velocity. The self-sustained tone might cause noise problems in the surroundings, cause losses due to plant shutdown, etc. The self-sustained tone has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The resonance frequencies obtained from the theory (without the flow) and the CFD simulations or the experiments are slightly different because of the absence or presence of the flow. Figure 1 shows that the slight increase of the resonance frequency occurs with an increase of the gap flow velocity [24]. The predicted SPL of the dominant tone at 740 Hz reasonably agrees with the measured one.…”
Section: Unsteady Cfd Simulationssupporting
confidence: 76%
See 3 more Smart Citations
“…The resonance frequencies obtained from the theory (without the flow) and the CFD simulations or the experiments are slightly different because of the absence or presence of the flow. Figure 1 shows that the slight increase of the resonance frequency occurs with an increase of the gap flow velocity [24]. The predicted SPL of the dominant tone at 740 Hz reasonably agrees with the measured one.…”
Section: Unsteady Cfd Simulationssupporting
confidence: 76%
“…Mori et al [24] performed compressible CFD simulations to capture the selfsustained tone and compare the simulation results with the measurements [13]. They confirmed that the self-sustained tone at the acoustic mode in the width direction of the duct occurs, and the sound pressure level does not follow the 5th power law when the gap velocity is high, as in the experiments.…”
Section: Unsteady Cfd Simulationsmentioning
confidence: 67%
See 2 more Smart Citations